Identification of Nobel Framework for Knowledge Portal in Higher Secondary Education Sector - Miri, Santosh Kumar; Sahu, Neelam (International Journal of Computer Sciences and Engineering, 2018)
Knowledge portal is highly integrative Knowledge Management System which provides a free and online subscription service. Day by day utility of knowledge portal is increasing. The backbone of education is higher secondary level in which student choices their stream. Every time a student requires syllabus, books, question papers etc. He/she waste time as well as money. It is available on the internet but they confused which is best. We decide to design and develop the knowledge portal for higher secondary sector. This portal will help the student, teachers as well as parents for the above purposes. How it will be more secure and powerful? Students, parents, teachers, syllabus, books, notes, unsold question papers etc are basic elements of the developing knowledge portal. Online lectures will be the root of the portal. Open source software’s are linsence free software. It is freely available on the Internet. In this paper, we will focus on and discuss the fundamental requirements for its development and also discuss portal elements.